Effects of exercise in people with multiple sclerosis: a systematic review and meta-analysis - Du, Liwen; Xi, Haoyu; Zhang, Shiyan; Zhou, Yilun; Tao, Xifeng; Lv, Yuanyuan; Hou, Xiao; Yu, Laikang (Frontiers in Public Health, 2024)
Background A growing body of studies have examined the effect of exercise in people with multiple sclerosis (MS), while findings of available studies were conflicting. This meta-analysis aimed to explore the effects of exercise on balance, walking ability, walking endurance, fatigue, and quality of life in people with MS. Methods We searched PubMed, Web of Science, Scopus, and Cochrane databases, through March 1, 2024. Inclusion criteria were: (1) RCTs; (2) included an intervention and control group; (3) had people with MS as study subjects; (4) had balance, walking ability, walking endurance, fatigue, or quality of life as the outcome measures. Exclusion criteria were: (1) non-English publications; (2) animal model publications; (3) review articles; and (4) conference articles. A meta-analysis was conducted to calculate weighted mean difference (WMD) and 95% confidence interval (CI). Cochrane risk assessment tool and Physiotherapy Evidence Database (PEDro) scale were used to evaluate the methodological quality of the included studies. Results Forty studies with a total of 56 exercise groups (n = 1,300) and 40 control groups (n = 827) were eligible for meta-analysis. Exercise significantly improved BBS (WMD, 3.77; 95% CI, 3.01 to 4.53, P < 0.00001), TUG (WMD, −1.33; 95% CI, −1.57 to −1.08, P < 0.00001), MSWS-12 (WMD, −2.57; 95% CI, −3.99 to −1.15, P = 0.0004), 6MWT (WMD, 25.56; 95% CI, 16.34 to 34.79, P < 0.00001), fatigue (WMD, −4.34; 95% CI, −5.83 to −2.84, P < 0.00001), and MSQOL-54 in people with MS (WMD, 11.80; 95% CI, 5.70 to 17.90, P = 0.0002) in people with MS. Subgroup analyses showed that aerobic exercise, resistance exercise, and multicomponent training were all effective in improving fatigue in people with MS, with resistance exercise being the most effective intervention type. In addition, a younger age was associated with a larger improvement in fatigue. Furthermore, aerobic exercise and multicomponent training were all effective in improving quality of life in people with MS, with aerobic exercise being the most effective intervention type. Conclusion Exercise had beneficial effects in improving balance, walking ability, walking endurance, fatigue, and quality of life in people with MS. Resistance exercise and aerobic exercise are the most effective interventions for improving fatigue and quality of life in people with MS, respectively. The effect of exercise on improving fatigue was associated with the age of the participants, with the younger age of the participants, the greater the improvement in fatigue. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=371056, identifier: CRD42022371056.